2022 European Thyroid Association Guideline for the management of pediatric Graves' disease. Issue 1 (1st January 2022) - Mooij, Christiaan F; Cheetham, Timothy D; Verburg, Frederik A; Eckstein, Anja; Pearce, Simon H; Léger, Juliane; van Trotsenburg, A S Paul
Abstract : Hyperthyroidism caused by Graves' disease (GD) is a relatively rare disease in children. Treatment options are the same as in adults – antithyroid drugs (ATD), radioactive iodine (RAI) or thyroid surgery, but the risks and benefits of each modality are different. The European Thyroid Association guideline provides new recommendations for the management of pediatric GD with and without orbitopathy. Clinicians should be alert that GD may present with behavioral changes or declining academic performance in children. Measurement of serum TSH receptor antibodies is recommended for all pediatric patients with hyperthyroidism. Management recommendations include the first-line use of a prolonged course of methimazole/carbimazole ATD treatment (3 years or more), a preference for dose titration instead of block and replace ATD, and to avoid propylthiouracil use. Where definitive treatment is required either total thyroidectomy or RAI is recommended, aiming for complete thyroid ablation with a personalized RAI activity. We recommend avoiding RAI in children under 10 years of age but favor surgery in patients with large goiter. Pediatric endocrinologists should be involved in all cases.